Efficacy and Safety of Metformin in Weight Loss in Bahraini Population - Sayed Mahmood Al-qallaf (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study is to explore the efficacy and safety of metformin in weight loss in Bahraini population. This study was a cross-sectional survey of 100 Bahraini patients aged 20 or more randomly selected. Using a self-administered questionnaire, volunteers answered questions regarding purposes, doses, side effects and sources of information of metformin and its impact on weight. Results have shown that 44 % of the participants have experienced weight loss after starting metformin. Weight loss reported was 1-5 kilograms by 45.4%and up to 10 Kg by 32 % of participants. Moreover, 23% of the patients have not experienced any adverse effects after starting metformin while some patients had abdominal pain (31 %) or loss of appetite (29 %).The findings of this study prove that metformin is an effective drug for weight loss. The results may have been influenced by other factors such as specific diet and physical exercises .In regard to safety, metformin was found to have a good safety profile as the side effects reported were mild to moderate and tended to subside after a period of use.
Keywords: Metformin, Weight Loss, slimming, Obesity.